Efectividad de un Programa Educativo en el Nivel de Conocimiento Materno Sobre Nutrición en preescolares - Carrascal Correa, Marina Soledad (2016)
This quantitative research, pre-experimental type was conducted in Initial Educational Institution No. 1639, 30 mothers of preschool for 3 years, during August- September 2016, in order to determine the effectiveness of "I educational program as healthy "in the level of knowledge of mothers about nutrition in preschool. The instrument was used for data collection: Survey to determine the level of maternal knowledge about nutrition in preschool, applied as pretest and posttest; being processed and analyzed by statistical test "t" of student information obtained. The results are presented in tables simple, double entry and graphs. After analysis we reached the following conclusions: Before the implementation of the educational program 53.2 percent of mothers presented average level of knowledge, 40 percent lower, and 6.8 percent higher. After application of the educational program .1 50 percent of mothers scored an average level of knowledge, 43.3 percent higher; and 6.6 percent lower. The educational program was highly signification to increase more than 40% in the level of knowledge about nutrition maternal preschool (p = 0.000). Keywords: Education program, nutrition knowledge, mothers of preschoolers.